Ectoparasites Infestation to Small Ruminants and Practical Attitudes among Farmers toward Acaricides Treatment in Central Region of Java, Indonesia - Titis Insyari’ati; Penny Humaidah Hamid; Endang Tri Rahayu; Diah Lutfiah Sugar; Nadya Nurvita Rahma; Shelly Kusumarini; Heri Kurnianto; April Hari Wardhana (Veterinary Sciences, 2024)
Ectoparasite infestations are one of the major problems affecting goat and sheep farming. Disease resulting from these infestations can cause changes in physical appearance, such as severe lesions on the skin, and economic consequences in the form of significantly reduced selling prices. This study aimed to determine the prevalence of ectoparasites in the Boyolali district, Central Java, Indonesia. A total of 651 sheep and goats were surveyed in this study. The parasites were collected via skin scraping, twister, or manually from clinically infected goats and sheep in traditional farms. All of the ectoparasites collected were successfully identified. The prevalence of ectoparasites in ruminants in Boyolali was 97.8% (637/651). The species make-up was as follows: Bovicola caprae 97.8% (637/651), Linognathus africanus 39% (254/651), Haemaphysalis bispinosa 3.5% (23/651), Ctenocephalides spp. 0.2% (1/651), and Sarcoptes scabiei 5.2% (34/651). The predilection sites were in the face, ear, and leg areas, and in the axillary, dorsal, abdomen, and scrotum regions of the surveyed animals. An evaluation of farmers’ attitudes to ectoparasites was performed using a questionnaire. The findings of this study imply that animals in the investigated area are highly exposed to ectoparasite infestations. Given the importance of ectoparasites in both livestock and human communities, specifically in the health domain, more research into appropriate control strategies is necessary.